The impact of globalization on the composition of government expenditures: evidence from panel data - Axel Dreher; Jan-Egbert Sturm; Heinrich W. Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2006)
According to the disciplining hypothesis, globalization restrains governments by inducing increased budgetary pressure. As a consequence, governments shift their expenditures in favour of transfers and subsidies and away from capital expenditures. This expenditure shift is potentially enhanced by citizens' preferences to be compensated for the risks of globalization ( compensation hypothesis ). Employing two different datasets and various measures of globalization, we analyze whether globalization has indeed influenced the composition of government expenditures. For a sample of 108 countries, we examine the development of four broad expenditure categories for the period 1970-2001: capital expenditures; expenditures for goods and services; interest payments; and subsidies and other current transfers. A second dataset provides a much more detailed classification: public expenditures, expenditures for defence, order, economic environment, housing, health, recreation, education, and social expenditures. However, this second data set is only available since 1990 - and only for the OECD countries. Our results show that globalization did not influence the composition of government expenditures.
Keywords: H7; H87; C23; 330; Globalisierung; Öffentliche Ausgaben; Steuerwettbewerb; Welt; OECD-Staaten